Application of intelligent agent for marketing intelligence in B2B environment. - Lee, Jenny. (2008)
This research paper investigates how intelligent agents can create marketing intelligence for organizations in the B2B environment. Oracle is used as a case study to illustrate the extent to which the intelligent agent, Landing Pad Technology (LPT), can create marketing intelligence for the organization.